Ossicular reconstruction of incudo-stapedial joint by glass ionomer—a study of 24 cases - Meenesh Juvekar (SpringerOpen, 2021)
Abstract Background Chronic otitis media is one of the major health issues worldwide resulting in partial or complete loss of conductive hearing mechanism including the tympanic membrane and ossicular assembly. The aim of the study is to assess hearing improvement after reconstructing the incudo-stapedial joint with glass ionomer cement. Here, a prospective observational study was done in a tertiary care hospital. Patients of chronic mucosal otitis media were operated, and intraoperatively incudo-stapedial joint discontinuity was restored using glass ionomer cement. Post-operative follow-up was done at 1-month, 3-month, 6-month, and 1-year intervals, and hearing was evaluated by doing pure tone audiometry with air conduction at 0.5, 1, 2, 3, 4, 6, and 8 kHz and bone conduction at 0.5, 1, 2, 3, and 4 kHz. Tabulation was done by calculating the air-bone gap in each patient. Results In our study, the patients showed statistically significant improvement in air conduction thresholds and near closure of air-bone gap post-operatively. The mean AC threshold is 15 dB with 91.67% patients having closure of ABG < 20 dB at the end of the 3rd month. Hearing was also evaluated at 6-month and 1-year intervals, which showed good improvement in hearing levels. Conclusions Glass ionomer is a simple, physiological, and cost-effective method of tympano-ossicular reconstruction with certain significant post-operative hearing improvement.